2007
DOI: 10.1124/jpet.107.127597
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Complex I Inhibitor Rotenone-Elicited Dopamine Redistribution from Vesicles to Cytosol in Human Dopaminergic SH-SY5Y Cells

Abstract: Parkinson's disease is a chronic neurodegenerative disorder characterized by loss of dopaminergic neurons in the substantia nigra. Rotenone, a pesticide, produces selective degeneration of dopaminergic neurons and motor dysfunction in rats. To determine the mechanisms underlying rotenoneinduced neuronal death, we investigated whether intracellular dopamine plays a role in rotenone (0.1-0.4 M)-induced apoptosis, using an in vitro model of human dopaminergic SH-SY5Y cells. The 40% decrease of dopamine content by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…A similar situation was observed in rat models of Parkinson's disease, whereas transfection with a yeast NADH dehydrogenase prevented the overproduction of ROS induced by rotenone (39,40). Recently, rotenone was described to stimulate ROS, protein carbonylation (61), and protein nitration, which was suggested to be a general signaling event underlying the formation of cytosolic protein aggregates, such as the Lewy bodies characteristic of Parkinson's disease (62). Rotenone also induces glutathione depletion (61; this work).…”
mentioning
confidence: 54%
“…A similar situation was observed in rat models of Parkinson's disease, whereas transfection with a yeast NADH dehydrogenase prevented the overproduction of ROS induced by rotenone (39,40). Recently, rotenone was described to stimulate ROS, protein carbonylation (61), and protein nitration, which was suggested to be a general signaling event underlying the formation of cytosolic protein aggregates, such as the Lewy bodies characteristic of Parkinson's disease (62). Rotenone also induces glutathione depletion (61; this work).…”
mentioning
confidence: 54%
“…Nitration of one or more tyrosine residues of TH was temporally associated with loss of enzymatic activity. The tyrosine nitration-mediated loss of TH activity parallels the decrease in dopamine levels, but this dopamine decrease alone is not sufficient to induce apoptosis because reserpine-induced depletion of intracellular dopamine does not lead to apoptosis (Watabe and Nakaki, 2007). Therefore, much less is known about the involvement of peroxynitrite in apoptosis induced by these toxins.…”
mentioning
confidence: 97%
“…4A). Using this model, we previously reported that the inhibition of rotenone-generated ROS or NO protected the cells from its toxicity (Watabe and Nakaki, 2007b;Watabe and Nakaki, 2008). Both L-NAME, an inhibitor of nitric oxide synthase (NOS), and N-acetylcysteine (NAC), a scavenger of ROS, suppressed the rotenone-induced increase in CK2 (Fig.…”
Section: Regulation Of Tubulin Acetylation By Ck2 In a Rotenone Modelmentioning
confidence: 99%
“…If this hypothesis was true, CK2 should be required for the proper formation of aggresomes. We previously investigated neuronal degeneration by using an in vitro rotenone model of human SH-SY5Y cells Watabe and Nakaki, 2007a;Watabe and Nakaki, 2007b;Watabe and Nakaki, 2008). Rotenone was used to generate oxidative stress in the cells 1521 CK2 regulates HDAC6 function and we analyzed aggresome formation.…”
Section: Regulation Of Tubulin Acetylation By Ck2 In a Rotenone Modelmentioning
confidence: 99%